SPANISH INTERNET USERS AND TOURISM: ANALYSIS OF ONLINE TOURIST BEHAVIOUR AMONG EXPERIENCED USERS - Pablo Garrido Pintado (Enlightening Tourism: A Pathmaking Journal)
Internet and E-commerce continue to expand in today's information and communication society. This research focuses on the most relevant characteristics of experienced Spanish Internet users. More specifically, this document concentrates on Internet users and travellers who buy or may buy in the future services offered by travel agents or other operators in the tourism industry. Data for this study was collected through questionnaires. Once collected, all data was subjected to statistical analysis in order to determine the demographic characteristics, values, uses and attitudes of subjects included in the sampling, as well as interactions between the above mentioned items. This process allowed us to reach sound conclusions.